Frequency of bullying behavior, sources and coping strategies among student nurses in karachi, Pakistan - Abdul Razzaque, Muhmooda; Sabir Hussain; Yasmeen Azad; Abdul Wahid; Abdul Razzak (Journal of University Medical & Dental College, 2023)
Background and objective: Bullying is being increasing day by day among health care professionals and specially nursing students (NS) are victimized due to their novelty in nursing profession. The objectives of this study were to find out frequencies of bullying behavior and its association with sources (perpetrators), and coping strategies among NS in Karachi, Pakistan. Methodology: This cross-sectional survey was conducted among NS and study setting was Dow (institute of Nursing and Midwifery) University of Health Sciences Karachi, Pakistan. Study duration was three months. Inclusion Criteria: NS who were bullied at least in the last 03 months. Exclusion criteria: unwilling participants and those who were absent at the time of data collection. Data was collected through an adapted questionnaire. The data was analyzed and entered into the SPSS version 26. Mean, standard deviations and percentages were used to analyze different forms, frequencies of bully behavior. A chi-square test was used to find the association of forms of bully behavior with sources(perpetrators), and coping strategies of bully. Result: Out of 300 NS, 64% of the NS were bullied repetitively at clinical duties and 45% were occasionally bullied at the nursing institute. Most frequent source of bully was seniors (57.0%) and a largely NS (51.7%) using coping strategy by overlooking bully which is significantly (p-value <0.05 ) associated with types of bully behavior. Conclusion: Present study highlighted that NS were experienced various forms of bully and mainly were bullied by seniors at clinicals and mostly they have overlooked bully incidence.